Efek Alprazolam Terhadap Jumlah Sel Leydig Mus Musculus Model Stres Kronik - Fedelita Aistania Putri; Renny I’tishom; Arifah Mustika (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Infertility is one of the stress stimulated for couple has been marriage. Misuse hypnotic drugs types of benzodiazepine in alprazolam as their primary drug problem. Benzodiazepine dependence can also affect the central nervous system that interfere with neurotransmitters dopamine and serotonin. Oxidative stress caused by exposure to benzodiazepines can cause interference pro-apoptotic protein balance and anti-apoptotic, with a marked increase in pro-apoptotic protein and a decrease in anti-apoptotic proteins such as in the Leydig cells. Oxidative stress stimulation activates the intrinsic apoptotic pathway. Objective: to see a decrease in the number of Leydig cells of male mice after exposure to the stress with cums method, and the mice would be given anti-anxiety medication therapy was alprazolam with maximum dossage. Materials and methods: The research subject using male mice (Mus musculus) strain Balb-c had aclimitazion proecess and randomize sampling. There were divided into three groups consisting of negative control group (K0), without stress and drugs when spermatogenesis time is positive control group (K1) and treatment group (K2). The mice get a daily alprazolam drugs (alganax) by gavage sonde with maximum dossage (4mg/kg/weight). The measurement’s do after obtained from the testis that has been cut crosswise and do the Hematoxylin-eosin (HE). Calculations carried out under a light microscope (Olympus BX 41). Results: Statistical test in Leydig cell showed that there was significant difference with kruskal walis p=0,000 (p<0,05). Conclusion: administration of alprazolam might decrease the number of Leydig cells of mice Mus musculus model of chronic stress